Quo Vadis Izin Pengelolaan Tambang Untuk Badan Usaha Milik Organisasi Kemasyarakatan Keagamaan (Analisis Hukum Peraturan Pemerintah Nomor 25 Tahun 2024 tentang Perubahan atas Peraturan Pemerintah Nomor 96 Tahun 2021 tentang Kegiatan Usaha Pertambangan Mineral dan Batubara) - Daniel Jonathan Parluhutan Pangaribuan (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Indonesia is blessed with abundant mineral and coal resources. The mineral and coal mining industry contributes around 8.57% of Indonesia's total Gross Domestic Product (GDP). The development of mining business activities with the provision of priority offers of Special Mining Business License Areas (WIUPK) to Business Entities Owned by Religious Organizations (BUMOK).This paper aims to find out more in examining Government Regulation Number 25 of 2024 concerning Amendments to Government Regulation Number 96 of 2021 concerning Minerba Mining Business Activities from the legal objectives of justice, expediency and legal certainty. This research is a normative research with a regulatory approach and analytical approach and analyzed with qualitative normative analysis methods. The results of research and discussion in this paper show that the controversial regulation of Government Regulation No. 25 of 2024 concerning Amendments to Government Regulation No. 96 of 2021 concerning Minerba Mining Business Activities is in Article 83A which gives priority WIUPK minerba offers to BUMOK which can potentially provide unfair advantages and pollute healthy business competition. Article 83A of Government Regulation No. 25 of 2024 on the Amendment to Government Regulation No. 96 of 2021 on Mineral and Coal Mining Business Activities potentially violates the legal objectives of justice, expediency and legal certainty.